DESAIN MODUL PELESTARIAN EKOSISTEM MANGROVE SEBAGAI SUMBER BELAJAR KEANEKARAGAMAN HAYATI SEKOLAH MENENGAH ATAS - Nursal, Nursal; L.N. Firdaus, L.N. Firdaus; Ma’ruf, Rizky (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The need for contextual learning materials that are contextual and relevant to the characteristics of living systems that have authenticity and uniqueness to the natural environment in recent developments is increasingly felt important and urgent. This study aims to produce a design module for SMA Biology learning about the Conservation of Mangrove Ecosystems by The Orang Suku Laut in the Riau Archipelago. For this reason, a survey study in Penaah was conducted to obtain scientific facts and information as a module design material through a partially developed research method (only the Analysis and Design stage). Samples are determined through snowball sampling techniques. Primary data are collected through field observations and in-depth interviews. Secondary data is obtained through search results on printed and electronic documentation. Data were analyzed through qualitative-descriptive techniques. The results obtained show that most of the flora of the mangrove ecosystem is used for firewood, pillars of houses, traditional medicines. All fauna of the mangrove ecosystem are used as food ingredients. There are at least nine forms of local wisdom practiced The Orang Suku Laut in concerving mangrove ecosystem in Penaah Village. All scientific facts from the research can be utilized for the design of Biology Subjects Module for Class X using the Problem-Based Learning Model. However, before the Module Design is used on a broader scale, it is recommended that a feasibility and effectiveness test should be carried out on a limited scale.Key Words: High School Biology Learning Module, preservation of mangrove ecosystems, Orang Suku Laut, Penaah Village